Symbolic Systems And Their Function In Contemporary Iraqi Sculpure (Journal of the College of Basic Education, 2026)
The current study, "Symbolic Systems and Their Operations in Contemporary Iraqi Sculpture," represents a new formulation for expressing an understanding of the operations of contemporary Iraqi sculpture through the development of intellectual connotations. The researcher found it necessary to shed light on this aspect. We have adopted four chapters, the first of which includes: the research problem, its importance, the research objectives, and its limits, as well as defining terminology.The research aims to uncover the symbolic systems used in contemporary Iraqi sculpture and demonstrate the creative abilities of form through sculpture. As for the research problem: Contemporary Iraqi artists have used intellectual structures, moving away from expression through direct realistic form, and employing creative ideas through formal symbols that indicate the essence of the state we wish to express. Multiple meanings may be combined within a single sculptural term. The researcher sees the necessity of shedding light on this common angle in contemporary Iraqi sculpture. Research objectives: To reveal the Iraqi artist's (sculptor's) ability to achieve symbolic expressive power by employing ideas and liberating himself from the limits of expression, in addition to the discourses that can be achieved through symbols in a single sculptural form.